Supply market orientation: a dynamic capability of the purchasing and supply management function. Issue 1 (2nd October 2020) - Foerstl, Kai; Kähkönen, Anni-Kaisa; Blome, Constantin; Goellner, Matthias
Abstract : Purpose: This paper aims to conceptualize supply market orientation (SMO) for the purchasing and supply chain management function and discusses how SMO capabilities are developed and how their application differs within and across firms. This research can thus be used as a blueprint for the development of a SMO capability that accommodates a firm's unique contextual antecedents' profile. Design/methodology/approach: The qualitative research design comprises five in-depth case studies with 43 semi-structured interviews with large manufacturing and service firms. Findings: SMO is defined as the capability to exploit market intelligence to assess, integrate and reconfigure the heterogeneously dispersed resources in purchasing and supply chain management in a way that best reflects the peculiarities of a firm's supply environment. The empirical analysis shows that although SMO capabilities are configured similarly, their application varies across and within firms depending on the characteristics of a firm's purchasing categories and tasks. Hence, reactive versus proactive SMO application is contingent upon firm-level and purchasing category–level characteristics. Originality/value: The study uses the dynamic capabilities view as a theoretical background and provides empirical evidence and theoretical reasoning to elaborate and endorse SMO as a dynamic capability that firms need to have to compete in a complex and dynamic environment. The study provides guidance for supply chain managers on how to successfully develop and deploy a SMO capability.